(untitled) (Academicia Globe: Inderscience Research, 2021)
Academic and social skills in young children are dependent on effective communication. Children gain the language and communication skills needed to convey their wants, thoughts, and feelings in social interactions during their preschool years, as well as how to respond appropriately to others. They also learn to be socially competent persons through effective communication, developing respectful, good interactions and connections with others. This enables youngsters to gain knowledge about themselves, others, and the world around them. Early childhood teachers need to prioritize to teach communication skills early and strategically, particularly in preschool when aiding children acquire necessary the knowledge and skills to be successful in kindergarten and the primary grades. This article focuses on the importance of communication skills and discusses the way of promoting this competence.